Die Politische und Soziale Bedeutung der Naqsbandiyya in Mittelasien Im 15. Jahrhundert. - Paul, Jürgen.
1 online resource (288 pages)
Keywords: The Studies in the History and Culture of the Islamic Orient (STIO) is the series of “Supplements“ to the journal Der Islam. Both are published by the Section for the History and Culture of the Near East in the Asian-African Institute of the University of Hamburg. The Section was established in 1908, before the foundation of the University of Hamburg. Under its first Director, C.H. Becker, it was the first academic centre in Germany in which teaching and research concentrated on the historical and cultural aspects of the Islamic world, and not just on philological issues. Many of Germany's leading authorities in Islamic Studies have studied and/or taught here. The “Supplements“ have maintained the same high quality and met the same high demands as the journal Der Islam and have published numerous studies on the history and culture of the Islamic world which have represented milestones in their relevant fields. The “New Series“ of Supplements appearing since 2004 carries this tradition forward and provides a platform for publishing studies on the history and culture of the Islamic world from the beginnings of Islam up to the present day.